BARAGIAH KA KAMPUANG: Spirit Filantropis Perantau Sulit Air - Addiarrahman Addiarrahman (Turast: Jurnal Penelitian dan Pengabdian, 2013)
This research aims to explore the expression of “baragaiah ka kampuang” as a philantrophy spirit of parantauSulit Air. It is based on post modernism paradigm of development that to built sustainable development must beinvolve the local wisdom of certain society. In the other hands, that is being the models to actualize the Islamiceconomic system in the grassroots. This research use phenomenology approach in the perspective of in world lookingor insider. In this sense, subjectivity is a tool to reveal the value of philantrophy spirit that can’t be revealed byobjective approach. In deep, it is open to other research to explorer this issue by using out world looking or outsider.The research conclution are that philantrophy spirit of parantau Sulit Air is inspired by Minangkabau value.Nevertheless, althought that spirit has a impotant effect on the development in Nagari Sulit Air, in reality hasalso destructive effect, such as value degradation, materialistic, etc. So, it need to precondition to make it as themodels of economic development for the Sulit Air society. That is the transformation of mitos, logos, and ethos.